Gerakan Pemuda Sulawesi Tengah (GPST) di Poso, 1957-1963 : perjuangan anti Permesta dan pembentukan Provinsi Sulawesi Tengah - Haliadi Sadi, 1971-; Syakir Mahid, 1959-; M. Anas Ibrahim, 1946- (Yogyakarta : Ombak, 2007)
History of youth movements and political development in Poso, 1950-1957.
Includes bibliographical references (pages [265]-272).
Keywords: Gerakan Pemuda Sulawesi Tengah; Youth movements -- Indonesia -- Poso (Sulawesi Tengah) -- History; Youth movements -- Indonesia -- Sulawesi Tengah -- History; Youth -- Political activity -- Indonesia -- Poso (Sulawesi Tengah); Poso (Indonesia : Kabupaten) -- Politics and government; Poso (Indonesia : Kabupaten) -- History; Sulawesi Tengah (indonesia) -- Politics and government; Sulawesi Tengah (Indonesia) -- History